Time-domain equalizer for multicarrier systems in impulsive noise - Tan, Yee Chieh; Ramli, Nordin Bin; Chuah, Teong Chee (John Wiley & Sons, 2011)
In multicarrier communication systems, a time-domain equalizer (TEQ) can be applied to shorten the channel impulse response and to eliminate inter-symbol interference (ISI). However, the presence of impulsive noise in the channel may paralyze the operation of TEQs and subsequently lead to poor error performance. In this paper, a multicarrier receiver that incorporates a constant false alarm rate algorithm and an iterative estimation technique (CFAR-IET) in conjunction with a TEQ is proposed to increase the robustness of the receiver against impulsive noise. Furthermore, an improved version of the CFAR-IET-TEQ scheme, which uses the buffering, sorting, removing and amplitude averaging (BSRA) processes, is presented. Performance comparisons of the proposed schemes with the existing Gaussian-optimized schemes are made. Simulation results show that the BSRA-IET-TEQ scheme is an effective approach to reduce symbol error rate (SER) in impulsive channels while performing satisfactorily in Gaussian channels. Copyright (C) 2011 John Wiley & Sons, Ltd.